Pengaruh Kepuasan Pelanggan Terhadap Kinerja Pegawai PT. PLN (PERSERO) ULP Rengat Kota Tahun 2020 - Surya Akbar (JIAGANIS, 2021)
ABSTRACTThis research was conducted to determine and measure customer satisfaction on the performance of PT. PLN in the Rengat City area. Even though PLN is a State Owned Enterprise, in this case PLN is required to be able to provide services that can satisfy its customers. For this reason, PT. PLN (Persero) must pay attention to broader marketing aspects, including being responsive to customer complaints such as inaccurate meter recording by officers, inaccurate billing systems, payment systems that are long queues, customers are always threatened by power cuts and many others. In this case, the performance of PT. PLN (Persero) Rengat is influenced by various factors including service, responsiveness to disturbances, ease of payment of electricity bills, electrical installation procedures and many others.